The Role of Teachers and Islamic Activities In Developing The Character of Students - Munawaroh, Isniatun; Ali, Mohammad; Hernawan, Asep Herry (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
The purpose of this study is to investigate the role of the teacher who serves as a role model for developing the character of students at the junior high school level. The research method used is descriptive qualitative research. The participants involved in this study were school principals, deputy principals, teachers of Islamic religious education and PKN, guidance and counseling teachers, homeroom teachers, and students from three junior high schools in Bandung. Data is collected through several techniques, namely interviews, observation and documentation. Data were analyzed using an interactive model from Miles & Huberman which includes the steps of: data reduction, data presentation, and drawing conclusions. The research findings show that several aspects of the teacher's personality that can be role models in developing student character are the use of language, behavior, and personality. The values that can be learned from the teacher's example are honesty, responsibility, courtesy, tolerance, discipline, and caring. There are several factors that become inhibiting and supporting. Several supporting factors in developing student character include curriculum content standards, leadership, commitment, and togetherness. Factors that become obstacles to developing student character are the low level of parental concern, the apathy of teachers and students, and the use of funds that are not optimal.